India's blueprint for tackling opportunistic acquisitions during COVID-19, with Chinese firms in mind - Hetal Doshi; Sankalp Udgata (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
COVID-19 has compelled countries across the globe to implement major amendments in their FDI policies to curb opportunistic takeovers and acquisitions of their companies. This Perspective critically analyses the Indian government's FDI policy amendments and proposes certain changes in the policy to make it more aligned with its objective.
Keywords: 330